Event-Related Beta EEG Changes During Active, Passive Movement and Functional Electrical Stimulation of the Lower Limb - Qiu, Shuang; Yi, Weibo; Xu, Jiapeng; Qi, Hongzhi; Du, Jingang; Wang, Chunfang; He, Feng; Ming, Dong (IEEE transactions on neural systems and rehabilitation engineering, 2016)
A number of electroencephalographic (EEG) studies have reported on event-related desynchronization/synchronization (ERD/ERS) during active movements, passive movements, and the movements induced by functional electrical stimulation (FES). However, the quantitative differences in ERD values and affected frequency bands associated with the lower limb have not been discussed. The goal of this paper was to quantitatively compare the ERD patterns during active movement, passive movement and FES-induced movement of the lower limb. 64-channel EEG signals were recorded to investigate the brain oscillatory patterns during active movement, passive movement and FES-induced movement of the lower limb in twelve healthy subjects. And passive movement and FES-induced movement were also performed in a hemiplegic stroke patient. For healthy subjects, FES-induced movement presented significantly higher characteristic frequency of central beta ERD while there was no significant difference in ERD values compared with active or passive movement. Meanwhile, beta ERD values of FES-induced movement were significantly correlated with those of active movement, and spatial distribution of beta ERD pattern for FES-induced movement was more correlated with that for active movement. In addition, the stroke patient presented central ERD patterns during FES-induced movement, while no ERD with similar frequencies could be found during passive movement. This work implies that the EEG oscillatory pattern under FES-induced movement tends more towards active movement instead of passive movement. The quantification of ERD patterns could be expected as a potential technique to evaluate the brain response during FES-induced movement.